The Prevalence of Electroconvulsive Therapy Use Since 1973: A Meta-analysis. Issue 4 (December 2016) - Lesage, Alain; Lemasson, Morgane; Medina, Karen; Tsopmo, Jackson; Sebti, Nedjma; Potvin, Stephane; Patry, Simon
Abstract : Objectives: A formal meta-analysis of the use of electroconvulsive therapy (ECT) has never been conducted before in literature reviews or syntheses. Such a study would be hampered by heterogeneity and potential reporting biases. However, it would provide a single comparable measure to allow an analysis of statistical key dimensions such as trends across time and psychiatric resources available. It would also help planners and decision makers to set standards and benchmarks for national and regional guidelines for quality assurance and research in health services. Methods: We surveyed different databases for relevant studies, limited from 1973 to October 2013. Data were extracted independently by 4 reviewers. The articles retrieved were peerreviewed studies (data-based studies or surveys) presenting ECT population rates (annual patient rates calculated from the general population) or number of patients receiving ECT during or after 1973 and attending a psychiatric establishment (either hospitals or approved ECT delivery centers for inpatients and outpatients in well-defined geographic areas). Results: This meta-analysis includes a total of 18 studies from 12 countries. A composite event rate of 16.9/100, 000 inhabitants emerged, characterized by high heterogeneity. Across the countries assessed, the prevalence of ECT was higher in older studies. Conclusions: By its prevalence, ECT remains rare to exceptional as a specialist treatment for mental disorders. Heterogeneity across regions or countries could best be explained by insufficient standardization of ECT procedures and practices. Linked health databases and audits could help strengthen the effectiveness of ECT in relation to primary outcomes such as suicide and help determine the gap in ECT provision, if any. Abstract : Supplemental digital content is available in the text.